The Impact of Good Corporate Governance (GCG) Mechanisms on Financial Statement Fraud with Firm Size as a Moderating Variable - Aryani, Lilia; Andesto, Ronny (Dinasti International Journal of Management Science, 2025)
This study aims to determine the Effect of Good Corporate Governance (GCG) Mechanisms on Financial Statement Fraud with Firm Size as a Moderating Variable. The population in this study were Primary Consumer Goods Sector Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) during 2020 - 2022. There were 210 samples selected using the purposive sampling method. The tool used in this study is Econometrical Views (Eviews) 10. The results of this study indicate that independent commissioner has a negative impact on financial statement fraud. Audit committee, institutional ownership, and managerial ownership have no impact on financial statement fraud. Firm size is able to moderate the impact of independent commissioner on financial statement fraud. Firm size is unable to moderate the impact of audit committee on financial statement fraud, firm size is unable to moderate the impact of institutional ownership on financial statement fraud, and firm size is unable to moderate the impact of managerial ownership on financial statement fraud.